PENYUSUNAN MODEL PERANGKAT LUNAK SEHATI ( SEHAT SUAMI DAN ISTRI ) UNTUK MEMBANTU PEMILIHAN ALAT KONTRASEPSI YANG COCOK BAGI PASUTRI BERBASIS EXPERT SYSTEM - SM Santi Winarsih, Retno Palupi (STMIK Sinar Nusantara, 2017)
According to Muhammad Arhami (2005), Expert systems are computer programs that are designated as providers of advice and aids in problem solving in various areas of particular specialization. The main purpose of the expert system is not to replace the position of an expert or experts, but only to popularize the knowledge and experience of experts are very rare. With the help of an expert system even laymen can eventually use this expert system to solve problems and take decisions usually by an expert While the definition of contraception by Prof.Dr. Sarwono Prawiroharjo are attempts to prevent pregnancy. Efforts could be temporary, can also be permanent. Permanent sterilization or contraception can be called stable.The purpose of this research is to develop a software model SEHATI to assist with selection of suitable contraceptives for married couples-based expert system. With this program are expected to society could be helped choose a contraceptive that is safe and appropriate without having met with the officer kesehatab. For health workers themselves increasingly assisted in this socialization of the use of contraceptives. The stages are done in this study systematically is starting with the stage of literature to find references supporters then gather data, identify and konseptualisiasi to determine the limits of the problem and experts involved, then formalize include manufacturing knowledge base that relate to the topic, determining inference method, followed by making the database design, new hereinafter do modeling software SEHATI to assist with selection of appropriate contraception for married couples-based expert system.In addition to producing the software modeling SEHATI to assist with selection of suitable contraceptives for married couples-based expert system that enriches the scientific work, outcomes obtained from this study is the enrichment materials teaching materials on expert systems and local scientific journals.Keywords: expert system, contraception, sterilization.